Evaluation of the physiological, hematological and biochemical profile related to the physiology of the exercise of horse submitted the lace modality - Menegatti, Rayssa Ludmila (2022)
The objective of this research was to verify the physiological, hematological and biochemical parameters of horses submitted to the lace modality in the State of Mato Grosso do Sul. Six males and two females were evaluated in two moments, before and after the exercise, characterized as M0 and M1. Regarding the physiological parameters, referring to rectal temperature, heart rate and respiratory rate in the M0 were (37,23 ± 0,25, 42,75± 6,22 and 29,75 ± 8,77), respectively, while in the M1 (37,97 ± 0,34, 64,35 ± 13,34, 60,87 ± 11,28), showing an increase after the loop test. In the erythrogram, only a change in the VCM result was observed after the exercise, as it occurs due to the increase of the erythrocytes and the release of young erythrocytes by the bone marrow. As for the biochemical parameters, there was an increase in M1 only in the result of the measurement of aspartate aminotransferase (AST) and reduction of blood glucose. The results showed that physiological, hematological and biochemical changes occurred after the tests in horses, due to the physiological requirements for the equine exercise. The highest changes were observed in the physiological results, as well as the VCM, AST, LDH, CK and blood glucose of the horses submitted to the tie test in this work.